2015
DOI: 10.14639/0392-100x-105513
|View full text |Cite
|
Sign up to set email alerts
|

Scleroterapia con bleomicina per malformazioni linfatiche dopo fallimento dell’escissione chirurgica: caso clinico

Abstract: Le malformazioni linfatiche (LMS) sono masse cistiche benigne derivanti dallo sviluppo anormale dei canali linfatici. Le malformazioni linfatiche interessano principalmente il distretto testa-collo. L’asportazione chirurgica di malformazioni linfatiche è seguita da un alto tasso di recidiva e vi è un elevato rischio di complicanze. La bleomicina è un farmaco antineoplastico approvato. Tale farmaco può essere usato come agente sclerosante nelle anomalie vascolari. Presentiamo il caso di un bambino sottoposto a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…The skin fibrosis model was prepared by subcutaneous injection of bleomycin (20 μg/mice) into the mice (Figure A). Prior reports confirmed that this dose is safe for mice, as no severe toxicity or side effects were observed during the preparation of the animal model. , NAVI treatments were started on day 14. The treatment groups were as follows: untreated, COA (50%), NAVI (50 μM), and COA (50%)/NAVI (50 μM).…”
Section: Resultsmentioning
confidence: 99%
“…The skin fibrosis model was prepared by subcutaneous injection of bleomycin (20 μg/mice) into the mice (Figure A). Prior reports confirmed that this dose is safe for mice, as no severe toxicity or side effects were observed during the preparation of the animal model. , NAVI treatments were started on day 14. The treatment groups were as follows: untreated, COA (50%), NAVI (50 μM), and COA (50%)/NAVI (50 μM).…”
Section: Resultsmentioning
confidence: 99%
“…The potential risks associated with bleomycin include pulmonary fibrosis, anaphylaxis and hyperpigmentation of the skin. 24 In comparison, doxycycline is relatively inexpensive and can be easily prepared; it is widely available in many ophthalmic centres. 16 Doxycycline may be considered as a safe, effective and cheaper alternative for bleomycin in the treatment of periorbital LMs.…”
Section: Discussionmentioning
confidence: 99%
“…Given a localized lesion, surgery resection and sclerotherapy are always the main choices for the management of both macro and mixed cLM (3,(16)(17)(18)(19). However, a series of cLM cases treated by surgery or sclerotherapy suffer from limited efficacy or local recurrence, especially for the cLM at the cervicofacial region, axilla, and joints.…”
Section: Discussionmentioning
confidence: 99%